Seismic reflection profile AWI-20080010 recorded in 2008, Southeastern Arctic Ocean - Weigelt, Estella; Geissler, Wolfram H (PANGAEA, 2022)
The data set provides unprocessed and processed seismic reflection data collected during Expedition PS72 (ARK-XXIII/3) onboard RV Polarstern in the southeastern Arctic Ocean in 2008. Detailed data acquisition parameters for the profile are documented in the expedition report (Jokat, 2015). Metadata, recording parameters, and the seismic data processing sequence are documented in the EBCDIC-Headers enclosed in the seg-y files. Navigation information is included in the seg-y headers, and in the CDP-SHOT-latitude-longitude file (see data product). A ReadMe file additionally lists the metadata and recording parameters for the seismic profile. The data set is grouped into three categories: 1. Raw data comprise (a) navigation data with date, time, and coordinates, (b) a shot list of date, time and shot-number, and (c) demultiplexed seismic data in seg-y format. Please note: for some very short consecutive profiles the demultiplexed raw data still are merged in one file. 2. Primary data consist of (a) CDP-sorted data in seg-y format, and (b) navigational data in a conventional UKOOA- file. 3. The data product is provided as (a) stacked or time-migrated version of the seismic profile in seg-y format and (b) a list with CDP and SHOT numbers as well as geographical coordinates. Please note that the low-frequency reflector running parallel to the seafloor at a depth of about 190 ms (~150 m) does not appear to be a ghost or bubble signal. It is likely an artifact created during acquisition that was not removed.
Keywords: Arctic Ocean; AWI Geophysics; Polarstern; Seismic reflection data